Detection of cytokine activated chondrocytes in arthritic joints from pigs infected with Erysipelothrix rhusiopathiae. Issue 8 (August 1992) - Davies, M E; Horner, A; Franz, B; Schuberth, H J
Abstract : Chronic polyarthritis was induced in pigs by injection of Erysipelothrix rhusiopathiae and the in vivo activation of chondrocytes by cytokines was then investigated in the affected joints by immunocytochemistry. A polyclonal antiserum which recognises surface markers on in vitro interleukin 1 activated porcine chondrocytes was used to detect activated chondrocytes in all zones of the cartilage from diseased joints. In contrast, cartilage removed from an unaffected joint in the same animal showed no chondrocyte activation. Inflammatory synovial tissue removed from diseased joints and cocultured with cartilage from the unaffected joint induced activation of adjacent chondrocytes. The presence of interleukin 1 in the inflammatory cells of the synovium was confirmed and major histocompatibility complex (MHC) class II antigens were detected as a marker of synovial activation. Chondrocytes were found not to express class II antigens in cartilage from either the diseased or the unaffected joint. These observations show that the porcine erysipelas model of arthritis will be useful in facilitating a novel approach to monitoring the behaviour of individual chondrocytes under pathophysiological conditions.